1999
DOI: 10.1139/x99-063
|View full text |Cite
|
Sign up to set email alerts
|

Understory plant community response after 23 years of hardwood control treatments in natural long leaf pine (Pinus palustris) forests

Abstract: In 1973, a study was established in south-central Alabama, U.S.A., to determine the effects of hardwood control treatments on understory succession and overstory growth in natural stands of longleaf pine (Pinus palustris Mill.). The treatments were seasonal biennial burns and a no-burn check, each combined with three supplemental hardwood control treatments (one-time chemical, periodic mechanical, and untreated check). Green vegetation less than 1 cm DBH and organic litter were destructively sampled to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 3 publications
2
42
1
1
Order By: Relevance
“…Fire alone can reduce above-ground L. japonica density temporarily, but it readily resprouts from the roots allowing it to rapidly replace damaged tissues following a typical prescribed fire [26,28,73], although repeated fires and high intensity fire have been shown to reduce overall L. japonica abundance in several studies [74][75][76]. Management of uninvaded areas with prescribed fires can decrease the likelihood of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Fire alone can reduce above-ground L. japonica density temporarily, but it readily resprouts from the roots allowing it to rapidly replace damaged tissues following a typical prescribed fire [26,28,73], although repeated fires and high intensity fire have been shown to reduce overall L. japonica abundance in several studies [74][75][76]. Management of uninvaded areas with prescribed fires can decrease the likelihood of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In uplands, although localized expansion of southern red oak and bluejack oak seedlings and saplings created smaller spots where competition for resources may be higher, large herbaceous-dominated areas still existed where longleaf pine seedlings could become established. Two additional cycles of prescribed fire decreased oak cover, thus discouraging these young hardwoods from ascending to the canopy and gaining dominance in the forest (Glitzenstein et al, 1995;Kush et al, 1999;Provencher et al, 2001). As highly-resilient disturbancedependent ecosystems (Stanturf et al, 2007;Outcalt, 2008), longleaf pine forests on both sites appear well adapted to management that includes frequent cycles of prescribed surface fire and periodic partial reduction of the forest canopy through selection systems and shelterwood methods.…”
Section: Contrasting Dynamics On Differing Sitesmentioning
confidence: 99%
“…Eight years after the reintroduction of fire, litter, partially decomposing litter, and humus decreased to 3.4, 12.7, and 14.0 Mg ha -1 , respectively (Kush and Meldahl 2006). Biennial burning has been reported to decrease organic litter biomass by as much as 66% (Kush et al 1999), andHaywood et al (2004) reported that burning removed over half of the available fuels. There appears to be little influence of fire on forest floor fuels in this study, probably because each stand was only recently burned once and single burns have been reported to show little change in fuel conditions (Haywood et al 2004).…”
Section: Volume 30 (2) 2010mentioning
confidence: 99%